2001
DOI: 10.1159/000046722
|View full text |Cite
|
Sign up to set email alerts
|

LDL and HDL Oxidation and Fatty Acid Composition in Vegetarians

Abstract: The oxidation of low-density lipoproteins (LDL) and high-density lipoproteins (HDL) and fatty acid composition, which may affect the resistance of lipoproteins to oxidation, were determined in 24 lacto-ovo vegetarians. Vegetarian diets contain more essential polyunsaturated fatty acids (PUFAs). Therefore, the relationship between LDL and HDL oxidation resistance measured by the kinetics of the formation of fatty acid conjugated dienes (lag time, maximal rate of oxidation and maximal amount of conjugated dienes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
(10 reference statements)
4
11
0
Order By: Relevance
“…This finding supports the hypothesis that HDL is more susceptible to oxidation than LDL (43,44). This may relate to the higher antioxidant content of LDL (7,45), which delays lipid peroxide formation.…”
Section: Discussionsupporting
confidence: 87%
“…This finding supports the hypothesis that HDL is more susceptible to oxidation than LDL (43,44). This may relate to the higher antioxidant content of LDL (7,45), which delays lipid peroxide formation.…”
Section: Discussionsupporting
confidence: 87%
“…Such a relation has been already shown in humans fed sunflower oil (38). It was then related to the value of the PI: This latter parameter indeed accurately reflects the degree of unsaturation of FA and estimates the concentration of bisallylic hydrogen atoms able to interact with free radicals (23). This could explain why the production of CD in lipoproteins tended to be higher in steers given linseed oil (18:3n-3) than in steers given sunflower oil (18:2n-6).…”
Section: Discussionmentioning
confidence: 54%
“…This is primarily because IsoP is a primary measure of lipid peroxidation. Specifically, HDL is the major lipoprotein carrier for IsoP (Proudfoot et al, 2009) and is more susceptible to oxidation than LDL (Raveh et al, 2000;Nagyova et al, 2001), which is consistent with the observed positive correlation with IsoP in the standard care patient group over 12 months. Blood lipids may present a biological influence on plasma IsoP concentration, and therefore may need to be considered for the interpretation of oxidative stress.…”
Section: Discussionsupporting
confidence: 82%